Intellectual security in the shariah sciences curriculum at the intermediate level in tackling the contemporary challenges from the perspective of supervisors and the teachers of the shariah sciences curriculum - Refan, al-Qahtani Salman (Institute of Education, International Islamic University Malaysia, 2012)
The need for the role of Shariah science is so vital for educating the generation about Islamic teachings, and maintaining the nation's capabilities and intellectual security which, in contemporary times, is one of the crucial needs of the nation. Thus, security is one of the key requirements ofhuman's life and is necessary for constructing human societies. Indeed, security is a great indicator for nations' development, and society developments, and if security with all its types is deemed critical in each nation, then intellectual security is the most critical and the most crucial among these types. By achieving harmony and unity among intellect, methodology, conduct, objective and purpose intellectual security is eventually attained. Therefore, educational institutions are among the significant institutes of socialization that bear the responsibility of protecting the youth inte'Jlect against intellectual invasion. Based on the above fact, the government of Saudi Arabia paid ample attention to Shariah science, and teaching them to students at all levels of education. In light of the various variables the Saudi society endures, the need for immunity of students' intellect became urgent through due manipulation of subjects taught to support and maintain the intellectual security as well as development of behavioral attitudes, and training individuals to become effective in the society. Therefore, the researcher seeks to reaffirm the role Shariah science curriculum plays in enhancing the intellectual security of students. and strives to highlight the extent to which supervisors and teachers of Shariah science have been performing their duty in explaining and supporting those principles to students. The researcher concluded that the Shariah science curriculum contain inadequate amount of concepts about intellectual security, therefore, there is a need to increase the teachers in guidance and training as to encourage them focus on this aspect when teaching, instead of increasing the topics that discuss the intellectual security aspect in the Shariah science curriculum.